CARving the Path to Allogeneic CAR T Cell Therapy in Acute Myeloid Leukemia - Pasvolsky, Oren; Daher, May; Alatrash, Gheath; Marin, David; Daver, Naval; Ravandi, Farhad; Rezvani, Katy; Shpall, Elizabeth; Kebriaei, Partow (Frontiers in Oncology, 2022)
Despite advances in the understanding of the genetic landscape of acute myeloid leukemia (AML) and the addition of targeted biological and epigenetic therapies to the available armamentarium, achieving long-term disease-free survival remains an unmet need. Building on growing knowledge of the interactions between leukemic cells and their bone marrow microenvironment, strategies to battle AML by immunotherapy are under investigation. In the current review we describe the advances in immunotherapy for AML, with a focus on chimeric antigen receptor (CAR) T cell therapy. CARs constitute powerful immunologic modalities, with proven clinical success in B-Cell malignancies. We discuss the challenges and possible solutions for CAR T cell therapy development in AML, and examine the path currently being paved by preclinical and clinical efforts, from autologous to allogeneic products.